A kind of anti-ultraviolet bamboo fiber fabric and its preparation process

By attaching high weathering urethane resin and UV-resistant composition to bamboo fiber fabrics, the problems of the sustainability and short service life of existing bamboo fiber fabrics are solved, and a long-lasting and efficient UV-resistant effect is achieved.

CN118958008BActive Publication Date: 2025-03-07GUANGZHOU HUARUN GARMENT IND CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411061251.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-02
Publication Date
2025-03-07
Estimated Expiration
2044-08-02

AI Technical Summary

Technical Problem

The current UV-proof bamboo fiber fabrics have relatively short UV-resistant efficacy and service life, resulting in limited application in the field of outdoor sportswear.

Method used

The UV resistance performance of bamboo fiber fabrics is improved by attaching a highly weather-resistant urethane resin and an UV-resistant composition, including surface-doped modified titanium dioxide or a combination thereof, on the surface.

Benefits of technology

It achieves excellent UV resistance effect of bamboo fiber fabrics and significantly improves its durability of UV resistance. After 50 washes, it still maintains an anti-UV effect of ≥90%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004978444780000111
    Figure BDA0004978444780000111
  • Figure BDA0004978444780000121
    Figure BDA0004978444780000121
  • Figure BDA0004978444780000131
    Figure BDA0004978444780000131
Patent Text Reader

Abstract

The present application relates to the technical field of functional fabric preparation, in particular to an anti-ultraviolet bamboo fiber fabric and its preparation process. In an anti-ultraviolet bamboo fiber fabric, the surface of the bamboo fiber is attached with an anti-ultraviolet composition through a highly weather-resistant urethane resin; the anti-ultraviolet composition is a surface-modified titanium dioxide with or a surface-modified titanium dioxide with zinc oxide, titanium nitride, titanium oxynitride, silicon nitride, and titanium dioxide grafted porous silicon nitride; the highly weather-resistant urethane resin is formed by curing water-based highly weather-resistant polyurethane latex; the particle size of the highly weather-resistant polyurethane latex in the water-based highly weather-resistant polyurethane latex is 100-200nm, and the glass transition temperature Tg≤-25℃. The present application has excellent anti-ultraviolet effect and relatively long-lasting anti-ultraviolet performance, and can still maintain ≥90% of the anti-ultraviolet effect after 50 water washings.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of functional fabric preparation, and in particular to an anti-ultraviolet bamboo fiber fabric. Background Art

[0002] As the name implies, bamboo fiber is a cellulose fiber material obtained by artificial extraction from naturally grown bamboo. It has the advantages of being green and environmentally friendly, having good breathability and moisture absorption, antibacterial and deodorizing, strong wear resistance, and strong dyeability. Therefore, it has been developed by modern textile workers into a new generation of environmentally friendly fabrics - bamboo fiber fabrics. Compared with conventional chemical fiber fabrics, high-quality bamboo fiber fabrics have good skin-friendliness and wearing comfort, especially the excellent skin feel, which is deeply loved by consumers. Although consumers are keen on the skin-friendliness and wearing comfort of bamboo fiber fabrics, they find that the bamboo fiber fabrics on the current market are mainly used for underwear fabrics. Because the existing bamboo fiber fabrics have relatively poor UV protection performance, their development and application in the field of outdoor sportswear fabrics are limited. In order to improve the anti-ultraviolet performance of existing bamboo fiber fabrics, the existing technology adopts a dyeing and finishing method to attach an anti-ultraviolet agent to the surface of bamboo fiber. Common anti-ultraviolet agents include: benzotriazole anti-ultraviolet agents, benzophenone anti-ultraviolet agents, triazine anti-ultraviolet agents, titanium dioxide, zinc oxide, tin dioxide, aluminum oxide, white carbon black, carbon black, graphene, carbon nanotubes, calcium carbonate, zinc phosphate, hydrotalcite, etc.

[0003] At present, the most common anti-ultraviolet post-treatment is the dipping / padding method, in which the anti-ultraviolet agent and acrylic emulsion are evenly mixed to form an anti-ultraviolet post-treatment liquid, and the bamboo fiber fabric is dipped / padded in the anti-ultraviolet post-treatment liquid for a period of time and then rinsed and dried. Although the above-mentioned prior art scheme gives the bamboo fiber fabric a good anti-ultraviolet effect for a period of time, the duration of this anti-ultraviolet effect is short. After the season change, the anti-ultraviolet performance of the bamboo fiber fabric is only kept at 50-70% of the original anti-ultraviolet performance when it is placed and used again in the next year. Limited by the anti-ultraviolet aging performance of the binder-acrylic emulsion itself and the bonding strength with the bamboo fiber, with the increase of water-based times and time, the anti-ultraviolet agent attached to the surface of the bamboo fiber is easy to be separated, which leads to the obvious decline of its anti-ultraviolet effect. The efficacy sustainability and service life of the existing anti-ultraviolet bamboo fiber fabric are relatively short. Summary of the invention

[0004] In order to solve the problems of the durability of the anti-ultraviolet effect and the relatively short service life of the above-mentioned existing anti-ultraviolet bamboo fiber fabrics, the present application provides an anti-ultraviolet bamboo fiber fabric and a preparation process thereof.

[0005] The present application provides an anti-ultraviolet bamboo fiber fabric, which is realized by the following technical solutions:

[0006] The surface of bamboo fiber in an anti-ultraviolet bamboo fiber fabric is attached with an anti-ultraviolet composition through a highly weather-resistant urethane resin; the anti-ultraviolet composition is surface-doped modified titanium dioxide or surface-doped modified titanium dioxide combined with at least one of zinc oxide, titanium nitride, titanium oxynitride, silicon nitride, and titanium dioxide grafted porous silicon nitride; the highly weather-resistant urethane resin is formed by curing water-based highly weather-resistant polyurethane latex; the particle size of the highly weather-resistant polyurethane latex in the water-based highly weather-resistant polyurethane latex is 100-200nm, and the glass transition temperature Tg≤-25°C.

[0007] Preferably, the surface doped modified titanium dioxide comprises titanium dioxide with an average particle size of 0.5-5 μm and modified particles doped on the surface of titanium dioxide with an average particle size of 0.5-5 μm; the modified particles are one or a combination of nano-sized aluminum oxide particles, nano-sized zinc oxide particles, nano-sized iron oxide particles, and nano-sized magnesium oxide particles.

[0008] Preferably, the modified particles are nano-sized aluminum oxide particles and / or nano-sized magnesium oxide particles.

[0009] Preferably, the surface doped modified titanium dioxide comprises titanium dioxide with an average particle size of 0.5-5 μm and a single atomic-level metal doped on the surface of titanium dioxide with an average particle size of 0.5-5 μm; the single atomic-level metal is one or a combination of aluminum, zinc, iron, magnesium, and cerium.

[0010] Preferably, the single-atom-level metal is zinc and / or cerium; the loading rate of the single-atom-level metal is 0.5-2wt%.

[0011] Preferably, the single-atom-level metals are zinc and cerium, the mass ratio of single-atom-level zinc to single-atom-level cerium is 3:1, and the loading rate of the single-atom-level metal is 1-2wt%.

[0012] The present invention has excellent anti-ultraviolet effect and relatively long-lasting anti-ultraviolet performance, and can still maintain ≥90% of the anti-ultraviolet effect after 50 washings.

[0013] Preferably, the anti-ultraviolet composition is composed of surface-doped modified titanium dioxide and titanium dioxide grafted porous silicon nitride in a mass ratio of (3-7):1.

[0014] By adopting the above technical solution, the anti-ultraviolet effect of the prepared bamboo fiber fabric can be improved.

[0015] Preferably, the water-based highly weather-resistant polyurethane latex comprises deionized water, a salt-forming agent, acetone, an aliphatic diisocyanate, a catalyst, a chain extender, a polyol composition, an antioxidant, and a leveling agent; the salt-forming agent is ammonia water or triethylamine; the aliphatic diisocyanate is one or more combinations of IPDI, HDI, HMDI, HTDI, and TMDI; the catalyst is organic bismuth or organic tin; the chain extender is dimethylol propionic acid combined with at least one of 1,6-hexanediol, 1,4-butanediol, and tetrafluorobutanediol; the polyol composition comprises polycarbonate diol combined with hydroxyl-terminated silicone oil and / or hydroxyl-terminated methyl vinyl silicone oil.

[0016] Preferably, the preparation method of the water-based highly weather-resistant polyurethane latex is as follows: at a speed of 100 to 200 rpm and under nitrogen protection, a polyol composition, an aliphatic diisocyanate, an antioxidant, and a catalyst are sequentially added to a reaction kettle and stirred for 3 to 5 minutes, the temperature is raised to 92 to 98° C. and reacted for 3 to 5 hours, and then an accurately measured chain extender is added to continue to react at 92 to 98° C. for 2 to 4 hours, and then acetone is added to dilute and the viscosity is adjusted to between 4000 and 8000 mPa.s, and then a salt-forming agent is added to neutralize after cooling to 40 to 45° C., and then deionized water and a leveling agent are added to disperse by high-speed shearing, and finally acetone is removed by distillation to obtain a finished product of a water-based highly weather-resistant polyurethane latex with a solid content of 25 to 40%.

[0017] By adopting the above technical solution, the anti-ultraviolet effect and anti-ultraviolet durability of bamboo fiber fabrics can be effectively improved.

[0018] The preparation process of the anti-ultraviolet bamboo fiber fabric provided in the present application is realized by the following technical scheme:

[0019] A preparation process of an anti-ultraviolet bamboo fiber fabric comprises the following steps:

[0020] Step 1, preparation of water-based highly weather-resistant polyurethane latex;

[0021] At the same time, the anti-bamboo fiber fabric is subjected to enzymatic hydrolysis and low-temperature plasma treatment in sequence to obtain a surface-activated modified bamboo fiber fabric, and the surface-activated modified bamboo fiber fabric is immersed in a siloxane aqueous solution for ultrasonic dispersion treatment for 15-30 minutes, wherein the concentration of siloxane in the siloxane aqueous solution is 0.5-2wt%, and the siloxane includes at least one of aminosilane, epoxysilane, methacryloxysilane, and vinylsilane, and the surface-modified bamboo fiber fabric is obtained by drying after ultrasonic dispersion treatment;

[0022] Step 2, 3-5 parts of water-based high weather-resistant polyurethane latex, 15-20 parts of anti-ultraviolet composition, 0.1-0.2 parts of xanthan gum, and 75-80 parts of deionized water are mixed uniformly to prepare anti-ultraviolet post-solidification solution;

[0023] Step 3, immersing the surface-modified bamboo fiber fabric in step 1 in the anti-ultraviolet solution, heating to 80-95° C. and immersing for 30-60 minutes, washing and drying to obtain the finished anti-ultraviolet bamboo fiber fabric;

[0024] Alternatively, in step three, the anti-ultraviolet finishing liquid is applied to the front and back sides of the bamboo fiber fabric respectively, 2-6g of the anti-ultraviolet finishing liquid is applied to each gram of the bamboo fiber fabric, and after the coating is completed, the anti-ultraviolet bamboo fiber fabric is dried at 110-125° C. to obtain the finished product.

[0025] The preparation process provided in this application is relatively simple, and the difficulty of implementing the operation is relatively low, which facilitates industrial production.

[0026] In summary, this application has the following advantages:

[0027] 1. This application has excellent anti-ultraviolet effect and has relatively long-lasting anti-ultraviolet performance. After 50 washes, it can still maintain ≥90% of the anti-ultraviolet effect.

[0028] 2. The highly weather-resistant polyurethane latex in the anti-UV post-solution is bonded to the surface of the anti-UV composition due to the capillary effect of the anti-UV composition particles, and adjacent highly weather-resistant polyurethane latexes are not bonded to each other, thereby effectively improving the anti-UV effect and anti-UV durability of the bamboo fiber fabric, while reducing the production cost of the bamboo fiber fabric and improving production competitiveness.

[0029] 3. The preparation process provided in this application is relatively simple, and the difficulty of implementing the operation is relatively low, which facilitates industrial production. DETAILED DESCRIPTION

[0030] In order to further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples and comparative examples.

[0031] Example

[0032] The surface of bamboo fiber in the anti-ultraviolet bamboo fiber fabric is attached with an anti-ultraviolet composition via a highly weather-resistant urethane resin.

[0033] The anti-ultraviolet composition is surface-doped modified titanium dioxide or surface-doped modified titanium dioxide combined with at least one of zinc oxide, titanium nitride, titanium oxynitride, silicon nitride, and titanium dioxide grafted porous silicon nitride.

[0034] Preferably, the anti-ultraviolet composition is composed of surface-doped modified titanium dioxide and titanium dioxide grafted porous silicon nitride in a mass ratio of (3-7): 1. Further, the anti-ultraviolet composition is composed of surface-doped modified titanium dioxide and titanium dioxide grafted porous silicon nitride in a mass ratio of 4:1.

[0035] High weather-resistant urethane resin is formed by curing water-based high weather-resistant polyurethane latex. The particle size of high weather-resistant polyurethane latex in water-based high weather-resistant polyurethane latex is 100-200nm, and the glass transition temperature Tg≤-25℃.

[0036] Preferably, the surface-doped modified titanium dioxide comprises titanium dioxide with an average particle size of 0.5-5 μm and modified particles doped on the surface of titanium dioxide with an average particle size of 0.5-5 μm. The modified particles are one or more combinations of nano-sized aluminum oxide particles, nano-sized zinc oxide particles, nano-sized iron oxide particles, and nano-sized magnesium oxide particles. Further, the modified particles are nano-sized aluminum oxide particles and / or nano-sized magnesium oxide particles.

[0037] Preferably, the surface doped modified titanium dioxide comprises titanium dioxide with an average particle size of 0.5-5 μm and a single-atom-level metal doped on the surface of the titanium dioxide with an average particle size of 0.5-5 μm. The single-atom-level metal is one or more combinations of aluminum, zinc, iron, magnesium, and cerium. Further, the single-atom-level metal is zinc and / or cerium; the loading rate of the single-atom-level metal is 0.5-2wt%. Further, the single-atom-level metal is zinc and cerium, the mass ratio of single-atom-level zinc to single-atom-level cerium is 3:1, and the loading rate of the single-atom-level metal is 1-2wt%.

[0038] The water-based high-weather-resistant polyurethane latex comprises deionized water, a salt-forming agent, acetone, an aliphatic diisocyanate, a catalyst, a chain extender, a polyol composition, an antioxidant and a leveling agent.

[0039] The salt-forming grade is ammonia water or triethylamine.

[0040] The aliphatic diisocyanate is one or more combinations of IPDI, HDI, HMDI, HTDI and TMDI.

[0041] The catalyst is organic bismuth or organic tin.

[0042] The chain extender is dimethylol propionic acid combined with at least one of 1,6-hexanediol, 1,4-butanediol and tetrafluorobutanediol.

[0043] The polyol composition comprises polycarbonate diol, hydroxyl-terminated silicone oil and / or hydroxyl-terminated methyl vinyl silicone oil.

[0044] The preparation method of water-based high-weather-resistant polyurethane latex is as follows: at a rotation speed of 100-200 rpm and under nitrogen protection, a polyol composition, an aliphatic diisocyanate, an antioxidant and a catalyst are sequentially added into a reaction kettle and stirred for 3-5 minutes, the temperature is raised to 92-98° C. for reaction for 3-5 hours, and then a chain extender with accurate measurement is added to continue to react at 92-98° C. for 2-4 hours, and then acetone is added for dilution to adjust the viscosity to between 4000-8000 mPa.s, and then a salt-forming agent is added for neutralization after the temperature is lowered to 40-45° C., and then deionized water and a leveling agent are added for high-speed shear dispersion, and finally acetone is removed by distillation to obtain a finished product water-based high-weather-resistant polyurethane latex with a solid content of 25-40%.

[0045] A preparation process of an anti-ultraviolet bamboo fiber fabric comprises the following steps:

[0046] Step 1, preparation of water-based highly weather-resistant polyurethane latex;

[0047] At the same time, the anti-bamboo fiber fabric is subjected to enzymatic hydrolysis and low-temperature plasma treatment in sequence to obtain a surface-activated modified bamboo fiber fabric, and the surface-activated modified bamboo fiber fabric is immersed in a siloxane aqueous solution for ultrasonic dispersion treatment for 15-30 minutes, wherein the concentration of siloxane in the siloxane aqueous solution is 0.5-2wt%, and the siloxane includes at least one of aminosilane, epoxysilane, methacryloxysilane, and vinylsilane, and the surface-modified bamboo fiber fabric is obtained by drying after ultrasonic dispersion treatment;

[0048] Step 2, 3-5 parts of water-based high weather-resistant polyurethane latex, 15-20 parts of anti-ultraviolet composition, 0.1-0.2 parts of xanthan gum, and 75-80 parts of deionized water are mixed uniformly to prepare anti-ultraviolet post-solidification solution;

[0049] Step 3, immersing the surface-modified bamboo fiber fabric in step 1 in the anti-ultraviolet solution, heating to 80-95° C. and immersing for 30-60 minutes, washing and drying to obtain the finished anti-ultraviolet bamboo fiber fabric;

[0050] Alternatively, in step three, the anti-ultraviolet finishing liquid is applied to the front and back sides of the bamboo fiber fabric respectively, 2-6g of the anti-ultraviolet finishing liquid is applied to each gram of the bamboo fiber fabric, and after the coating is completed, the anti-ultraviolet bamboo fiber fabric is dried at 110-125° C. to obtain the finished product.

[0051] Embodiment 1: A kind of anti-ultraviolet bamboo fiber fabric has an anti-ultraviolet composition attached to the surface of bamboo fiber through a highly weather-resistant urethane resin. The anti-ultraviolet composition is surface-doped modified titanium dioxide. The surface-doped modified titanium dioxide includes 3000 mesh titanium dioxide and modified particles-nano-scale aluminum oxide particles fixedly doped on the surface of titanium dioxide.

[0052] The preparation method of surface doped modified titanium dioxide is as follows:

[0053] Step 1. Dissolve 23.4 g of aluminum nitrate nonahydrate in 1.0 L of distilled water and stir at 240 rpm for 30 min, then add 50 g of 3000 mesh Anada anatase titanium dioxide, maintain stirring at 240 rpm for 30 min, then add a 1 wt% sodium hydroxide aqueous solution until Al is completely precipitated, continue magnetic stirring for 1 h, and let stand for 24 h to obtain Al(OH)3 / TiO2 binary colloid;

[0054] Step 2. Wash the prepared Al(OH)3 / TiO2 binary colloid three times with distilled water, filter out the solid powder, and then place it in a vacuum drying oven at 105°C for 10 hours. Then, separate the dried solid and calcine it in a transfer atmosphere tube furnace. Heat it to 640°C in an air atmosphere and calcine it for 4 hours. Ball mill and sieve to obtain surface-doped nano-scale Al2O3 / T iO2 powder.

[0055] The water-based high weather-resistant polyurethane latex includes 2001g of deionized water, 22g of salt-forming agent triethylamine, 300g of acetone, 168.2g of aliphatic diisocyanate HD I, 0.16g of catalyst bismuth isooctanoate, 32.2g of dihydroxymethylpropionic acid, 60.27g of 1,6-hexanediol, 200g of polycarbonate diol with a molecular weight of 1000 (CD210 of Daicel of Japan, hydroxyl value 107-117mgKOH / g), 177.5g of hydroxyl-terminated silicone oil (double-end alcohol hydroxyl long-chain alkyl silicone oil IOTA-8865H of Anhui Aiyota Silicone Oil Co., Ltd., hydroxyl value 25.0KOHmg / g), 18g of antioxidant BHT, and 20g of leveling agent BYK-S706.

[0056] The preparation method of water-based highly weather-resistant polyurethane latex is as follows:.

[0057] A preparation process of an anti-ultraviolet bamboo fiber fabric comprises the following steps:

[0058] Step 1: Preparation of water-based high weather-resistant polyurethane latex: 177.5 g of double-terminal alcohol hydroxyl long-chain alkyl silicone oil IOTA-8865H, 168.2 g of aliphatic diisocyanate HD were added to the reactor in sequence at a speed of 200 rpm and under nitrogen protection. I. 18g of antioxidant BHT and 0.16g of bismuth isooctanoate were stirred and mixed for 5min, heated to 98°C for reaction for 1h, and then 200g of polycarbonate diol CD210 with a molecular weight of 1000 was added, and the reaction was continued at 98°C for 3h; then 60.27g of 1,6-hexanediol was added to adjust the temperature to 92°C for reaction for 1h, and then 32.2g of dimethylol propionic acid was added to react at 92°C for 1.5h. After the chain extender addition reaction was completed, acetone was added to the reactor 6 times, each time with an amount of 50g of acetone, and the viscosity was adjusted by dilution to 5785mPa.s. After cooling to 40°C, 22g of triethylamine was added for neutralization, and then 2001g of deionized water and 20g of BYK-S706 were added for high-speed shear dispersion, and finally acetone was removed by distillation to obtain a finished water-based high-weather-resistant polyurethane latex with a solid content of 30±0.2wt%;

[0059] At the same time, the anti-bamboo fiber fabric is subjected to enzymatic hydrolysis and low-temperature plasma treatment in turn to obtain surface activated modified bamboo fiber fabric.

[0060] The enzymatic hydrolysis treatment is as follows: 100 g of bamboo fiber fabric is placed in 5 L of cellulase solution with a specific activity of 150 U / g and a concentration of 50 g / L, fully immersed at 65°C for 30 min, washed three times with water, and dried for use;

[0061] The low-temperature plasma treatment is as follows: the bamboo fiber fabric that has completed the enzymatic hydrolysis treatment is placed in the EPDM low-temperature plasma surface treatment machine-PG-1000ZE, and the low-temperature plasma treatment is performed for 300 seconds at -5°C using compressed air, and the output working pressure is: 0.024MPa, and then the low-temperature plasma treatment is performed for 300 seconds at -5°C using compressed ammonia gas, and the output working pressure is: 0.016MPa to obtain the surface activated modified bamboo fiber fabric;

[0062] The surface activated bamboo fiber fabric was immersed in a siloxane aqueous solution (prepared with 6g of KH560 and 2g of KH550 in 1L of deionized solvent) and subjected to ultrasonic dispersion treatment for 20min, with an ultrasonic dispersion frequency of 34kHz and an ultrasonic dispersion power of 600W. After the ultrasonic dispersion treatment, the surface-modified bamboo fiber fabric was dried.

[0063] Step 2, 30g of a finished water-based high-weather-resistant polyurethane latex with a solid content of 30±0.2wt%, 150g of an anti-ultraviolet composition, 1g of xanthan gum, and 800g of deionized water are mixed uniformly to prepare an anti-ultraviolet solution;

[0064] Step 3, immersing the surface-modified bamboo fiber fabric in step 1 in the anti-ultraviolet finishing solution, heating to 95° C. and immersing for 45 minutes, washing five times and drying to obtain the finished anti-ultraviolet bamboo fiber fabric;

[0065] The difference between Example 2 and Example 1 is: Step three, apply the anti-ultraviolet finishing liquid to the front and back sides of the bamboo fiber fabric respectively, apply 4g of the anti-ultraviolet finishing liquid per gram of bamboo fiber fabric, and after the coating is completed, dry it at 120°C to obtain the finished anti-ultraviolet bamboo fiber fabric.

[0066] The difference between Example 3 and Example 1 is that the surface-modified bamboo fiber fabric in step 1 is immersed in the anti-ultraviolet finishing solution, heated to 95° C. and immersed for 30 minutes, washed five times and then dried to obtain the finished anti-ultraviolet bamboo fiber fabric.

[0067] The difference between Example 4 and Example 1 is that the surface-modified bamboo fiber fabric in step 1 is immersed in the anti-ultraviolet finishing solution, heated to 95° C. and immersed for 60 minutes, washed five times and then dried to obtain the finished anti-ultraviolet bamboo fiber fabric.

[0068] The difference between Example 5 and Example 2 is: Step three, apply the anti-ultraviolet finishing liquid to the front and back sides of the bamboo fiber fabric respectively, apply 2g of the anti-ultraviolet finishing liquid per gram of bamboo fiber fabric, and after the coating is completed, dry it at 120°C to obtain the finished anti-ultraviolet bamboo fiber fabric.

[0069] The difference between Example 6 and Example 2 is: Step three, apply the anti-ultraviolet finishing liquid to the front and back sides of the bamboo fiber fabric respectively, apply 6g of the anti-ultraviolet finishing liquid per gram of bamboo fiber fabric, and after coating, dry at 120°C to obtain the finished anti-ultraviolet bamboo fiber fabric.

[0070] The difference between Example 7 and Example 1 is: Step 2, 40g of the finished water-based high weather-resistant polyurethane latex with a solid content of 30±0.2wt%, 150g of the anti-ultraviolet composition, 1g of xanthan gum, and 800g of deionized water are mixed evenly to prepare the anti-ultraviolet post-solidification liquid.

[0071] The difference between Example 8 and Example 1 is: Step 2, 50g of the finished water-based high weather-resistant polyurethane latex with a solid content of 30±0.2wt%, 150g of the anti-ultraviolet composition, 1g of xanthan gum, and 800g of deionized water are mixed evenly to prepare the anti-ultraviolet post-solidification liquid.

[0072] The difference between Example 9 and Example 1 is: Step 2, 30g of the finished water-based high weather-resistant polyurethane latex with a solid content of 30±0.2wt%, 175g of the anti-ultraviolet composition, 1.2g of xanthan gum, and 800g of deionized water are mixed evenly to prepare the anti-ultraviolet post-solidification liquid.

[0073] The difference between Example 10 and Example 1 is: Step 2, 30g of the finished water-based high weather-resistant polyurethane latex with a solid content of 30±0.2wt%, 200g of the anti-ultraviolet composition, 1.5g of xanthan gum, and 800g of deionized water are mixed evenly to obtain the anti-ultraviolet post-solidification liquid.

[0074] The difference between Comparative Example 1 and Example 1 is that the surface doped modified titanium dioxide is replaced by 3000 mesh Anada anatase titanium dioxide, and the finished water-based high weather-resistant polyurethane latex is replaced by the commercially available brand Ruikos FS-WPU polymer water-based polyurethane with a solid content of 50%. In step 2 of the corresponding preparation method, 18g of FS-WPU polymer water-based polyurethane with a solid content of 50wt%, 150g of anti-ultraviolet composition, 1g of xanthan gum, and 800g of deionized water are mixed uniformly to obtain an anti-ultraviolet post-solidification solution.

[0075] The difference between Comparative Example 2 and Example 1 is that the surface doped and modified titanium dioxide is replaced by 3000 mesh Anada anatase titanium dioxide.

[0076] The difference between Comparative Example 3 and Example 1 is that the finished water-based high weather-resistant polyurethane latex replaces the commercially available brand FS-WPU high molecular water-based polyurethane of Ruikos.

[0077] The difference between Comparative Example 4 and Example 1 is that the surface-modified bamboo fiber fabric in step 1 is immersed in the anti-ultraviolet finishing solution, heated to 95° C. and immersed for 15 minutes, washed five times and then dried to obtain the finished anti-ultraviolet bamboo fiber fabric.

[0078] The difference between Comparative Example 5 and Example 1 is that the surface-modified bamboo fiber fabric in step 1 is immersed in the anti-ultraviolet finishing solution, heated to 95° C. and immersed for 70 minutes, washed five times and then dried to obtain the finished anti-ultraviolet bamboo fiber fabric.

[0079] The difference between Comparative Example 6 and Example 2 is: Step three, apply the anti-ultraviolet finishing liquid to the front and back sides of the bamboo fiber fabric respectively, apply 1g of the anti-ultraviolet finishing liquid per gram of bamboo fiber fabric, and after coating, dry at 120°C to obtain the finished anti-ultraviolet bamboo fiber fabric.

[0080] The difference between Comparative Example 7 and Example 2 is: Step three, apply the anti-ultraviolet finishing liquid to the front and back sides of the bamboo fiber fabric respectively, apply 8g of the anti-ultraviolet finishing liquid per gram of bamboo fiber fabric, and after coating, dry at 120°C to obtain the finished anti-ultraviolet bamboo fiber fabric.

[0081] The difference between Comparative Example 8 and Example 1 is as follows: Step 2: 20 g of a finished water-based high-weather-resistant polyurethane latex with a solid content of 30 ± 0.2 wt %, 150 g of an anti-ultraviolet composition, 1 g of xanthan gum, and 800 g of deionized water are mixed uniformly to obtain an anti-ultraviolet solution.

[0082] The difference between Comparative Example 9 and Example 1 is: Step 2, 60g of the finished water-based high weather-resistant polyurethane latex with a solid content of 30±0.2wt%, 150g of the anti-ultraviolet composition, 1g of xanthan gum, and 800g of deionized water are mixed evenly to prepare the anti-ultraviolet post-solidification liquid.

[0083] The difference between Comparative Example 10 and Example 1 is: Step 2, 30g of the finished water-based high weather-resistant polyurethane latex with a solid content of 30±0.2wt%, 100g of the anti-ultraviolet composition, 1.5g of xanthan gum, and 800g of deionized water are mixed evenly to prepare the anti-ultraviolet post-solidification liquid.

[0084] The difference between Comparative Example 11 and Example 1 is: Step 2, 30g of the finished water-based high weather-resistant polyurethane latex with a solid content of 30±0.2wt%, 300g of the anti-ultraviolet composition, 1.5g of xanthan gum, and 800g of deionized water are mixed evenly to prepare the anti-ultraviolet post-solidification liquid.

[0085] The difference between Comparative Example 12 and Example 1 is: Step 2, 30g of the finished water-based high weather-resistant polyurethane latex with a solid content of 30±0.2wt%, 1.5g of xanthan gum, and 800g of deionized water are mixed evenly to prepare an anti-ultraviolet post-treatment liquid.

[0086] Performance testing: 1. The anti-ultraviolet performance was tested according to GB / T 18830-2009 "Evaluation of the anti-ultraviolet performance of textiles". The standard for anti-ultraviolet textiles stipulates: UPF>40, T(UVA)<5%. 2. The anti-ultraviolet performance washing resistance test was based on the 4N program in GB / T 8629-2017 "Household washing and drying procedures for textile testing" after a cumulative washing of 50 times, and then tested according to GB / T18830-2009 "Evaluation of the anti-ultraviolet performance of textiles". 3. Durability of anti-ultraviolet performance: The anti-ultraviolet bamboo fiber fabrics in Examples 1-10 and Comparative Examples 1-12 were subjected to jungle tests, and UPF and T(UVA) were tested after aging in the jungle at 85°C and 80% humidity for 2 weeks, and the retention rates of UPF and T(UVA) were calculated. UPF value retention rate = (value n years ago - current value): value n years ago * 100; T (UVA) retention rate = 100 - (current value - value n years ago) ÷ current value * 100).

[0087] Table 1: Test parameters of UV-resistant bamboo fiber fabrics in Examples 1-10 and Comparative Examples 1-12

[0088]

[0089]

[0090] It can be seen from Examples 1-10 and Comparative Examples 1-3 and Table 1 that the anti-ultraviolet liquid formed by the water-based high weather-resistant polyurethane latex and the anti-ultraviolet composition in the present application combined with the provided impregnation or coating process, the prepared bamboo fiber fabric has excellent anti-ultraviolet effect and has a relatively long-lasting anti-ultraviolet performance. After 50 washings, the anti-ultraviolet effect can still be maintained at ≥90%, and the anti-ultraviolet effect retention rate is ≥88% after 2 weeks of simulated aging jungle.

[0091] Combining Examples 1, 3-4 and Comparative Examples 4-5 with Table 1, it can be seen that the bamboo fiber fabric prepared by immersion at 95°C for 30-60 min has excellent comprehensive anti-ultraviolet performance, and too long immersion time will damage the bamboo fiber structure.

[0092] Combining Examples 2, 5-6 and Comparative Examples 6-7 with Table 1, it can be seen that in the coating process: 2-5g of anti-ultraviolet liquid is preferably applied per gram of bamboo fiber fabric. Too little will affect the anti-ultraviolet effect, and too much will affect the water resistance.

[0093] Combining Examples 1, 7-8 and Comparative Examples 8-9 with Table 1, it can be seen that in the formula of the anti-ultraviolet liquid: 150g of the anti-ultraviolet composition is used with 30-50g of the aqueous high weather-resistant polyurethane latex, which can ensure that the prepared bamboo fiber fabric has excellent anti-ultraviolet effect and has a relatively long-lasting anti-ultraviolet performance.

[0094] Combining Examples 1, 9-10 and Comparative Examples 10-12 and Table 1, it can be seen that in the formula of the anti-ultraviolet liquid: 30g of water-based high weather-resistant polyurethane latex is used in combination with 150-200g of the anti-ultraviolet composition, which can ensure that the prepared bamboo fiber fabric has excellent anti-ultraviolet effect and has a relatively long-lasting anti-ultraviolet performance. If the anti-ultraviolet composition is added too little, the anti-ultraviolet effect is low, and if the anti-ultraviolet composition is added too much, the water washing resistance and weather resistance will decrease.

[0095] It can be seen from the combination of Examples 1-10 and Comparative Examples 1-3 and Table 1 that the preferred parameters can be screened out to obtain Example 11.

[0096] The difference between Example 11 and Example 2 is: Step 2, 40g of the finished water-based high weather-resistant polyurethane latex with a solid content of 30±0.2wt%, 175g of the anti-ultraviolet composition, 1.2g of xanthan gum, and 800g of deionized water are mixed uniformly to obtain the anti-ultraviolet post-solidification liquid.

[0097] The difference between Example 12 and Example 1 is that the anti-ultraviolet composition is composed of surface-doped modified titanium dioxide and zinc oxide, and the mass ratio of surface-doped modified titanium dioxide to zinc oxide is 4: 1. The zinc oxide used is selected from 800 mesh zinc oxide produced by Guangdong Yuanlei Powder Co., Ltd.

[0098] The difference between Example 13 and Example 1 is that the anti-ultraviolet composition is composed of surface-doped modified titanium dioxide and zinc oxide, and the mass ratio of surface-doped modified titanium dioxide to titanium nitride is 4: 1. The titanium nitride used is selected from 2000 mesh titanium nitride powder of Qinghe Chaotai Metal Materials Co., Ltd.

[0099] The difference between Example 14 and Example 1 is that the anti-ultraviolet composition is composed of surface-doped modified titanium dioxide and zinc oxide, and the mass ratio of surface-doped modified titanium dioxide to titanium oxynitride is 4: 1. The titanium oxynitride used is selected from CW-TiON-001 nano titanium oxynitride produced by Shanghai Chaowei Nanotechnology Co., Ltd.

[0100] The difference between Example 15 and Example 1 is that the anti-ultraviolet composition is composed of surface-doped modified titanium dioxide and zinc oxide, and the mass ratio of surface-doped modified titanium dioxide to silicon nitride is 4: 1. The silicon nitride used is ultrafine silicon nitride with a particle size of 1-3 μm selected from Guangdong Wengjiang Chemical Reagent Co., Ltd.

[0101] The difference between Example 16 and Example 1 is that the anti-ultraviolet composition is composed of surface-doped modified titanium dioxide and zinc oxide, and the mass ratio of surface-doped modified titanium dioxide to titanium dioxide grafted porous silicon nitride is 4: 1. Titanium dioxide grafted porous silicon nitride is selected from TiO2-g-Si3N4 provided by Xi'an Ruixi Biotechnology Co., Ltd.

[0102] Table 2: Test parameter table of UV-resistant bamboo fiber fabrics in Example 11 and Examples 12-16

[0103]

[0104]

[0105] It can be seen from Example 11 and Examples 12-16 and Table 2 that the anti-ultraviolet composition formed by the surface-doped modified titanium dioxide and one of zinc oxide, titanium nitride, titanium oxynitride, silicon nitride, and titanium dioxide grafted porous silicon nitride has excellent anti-ultraviolet effect and relatively long-lasting anti-ultraviolet performance.

[0106] The difference between Example 17 and Example 11 is that the anti-ultraviolet composition is titanium dioxide modified by surface doping with nano-sized magnesium oxide particles. The titanium dioxide modified by surface doping with nano-sized magnesium oxide particles includes 3000 mesh titanium dioxide and modified particles-nano-sized magnesium oxide particles fixedly doped on the surface of titanium dioxide.

[0107] The preparation method of titanium dioxide modified by surface doping with nano-sized magnesium oxide particles is as follows: Step 1. Dissolve 16.7 g of aluminum nitrate nonahydrate in 1.0 L of distilled water and stir at 240 rpm for 30 min, then add 50 g of 3000 mesh Anada anatase titanium dioxide, maintain stirring at 240 rpm for 30 min, then add a 1 wt% sodium hydroxide aqueous solution, continue magnetic stirring for 1 h until Mg is completely precipitated, and let stand for 24 h to obtain Mg(OH)2 / TiO2 binary colloid;

[0108] Step 2. Wash the prepared Mg(OH)2 / TiO2 binary colloid three times with distilled water, filter out the solid powder, and then place it in a vacuum drying oven at 105°C for 10 hours. Then, separate the dried solid and calcine it in a transfer atmosphere tube furnace. Heat it to 640°C in an air atmosphere and calcine it for 4 hours. Ball mill and sieve to obtain surface-doped nano-scale MgO2 / TiO2 powder.

[0109] The difference between Example 18 and Example 11 is that the anti-ultraviolet composition is the titanium dioxide modified by surface doped with nano-scale magnesium oxide particles in Example 17 and the titanium dioxide modified by surface doped with nano-scale aluminum oxide particles in Example 1, and the mass ratio of the titanium dioxide modified by surface doped with nano-scale magnesium oxide particles in Example 17 and the titanium dioxide modified by surface doped with nano-scale aluminum oxide particles in Example 1 is 1:1.

[0110] Table 3: Test parameter table of UV-resistant bamboo fiber fabrics in Example 11 and Examples 17-18

[0111]

[0112] It can be seen from Example 11 and Examples 17-18 and Table 3 that the anti-ultraviolet composition formed by titanium dioxide modified by surface doped with nano-sized magnesium oxide particles and titanium dioxide modified by surface doped with nano-sized aluminum oxide particles has excellent anti-ultraviolet effect and relatively long-lasting anti-ultraviolet performance.

[0113] The difference between Example 19 and Example 11 is that the anti-ultraviolet composition is titanium dioxide doped with surface single-atom metal cerium, the carrier is 3000 mesh Anada anatase titanium dioxide, and the loading rate of single-atom metal is 0.5wt%. The titanium dioxide doped with surface single-atom metal cerium is customized from Guangxi Liankehua New Materials Co., Ltd.

[0114] The difference between Example 20 and Example 19 is that the anti-ultraviolet composition is titanium dioxide doped with surface single-atom metal aluminum, the carrier is 3000 mesh Anada anatase titanium dioxide, and the loading rate of single-atom metal is 0.5wt%.

[0115] The difference between Example 21 and Example 19 is that the anti-ultraviolet composition is titanium dioxide doped with surface single-atom metal iron, the carrier is 3000 mesh Anada anatase titanium dioxide, and the loading rate of single-atom metal is 0.5wt%.

[0116] The difference between Example 22 and Example 19 is that the anti-ultraviolet composition is titanium dioxide doped with surface single-atom metal zinc, the carrier is 3000 mesh Anada anatase titanium dioxide, and the loading rate of single-atom metal is 0.5wt%.

[0117] The difference between Example 23 and Example 19 is that the anti-ultraviolet composition is titanium dioxide doped with surface single-atom metal magnesium, the carrier is 3000 mesh Anada anatase titanium dioxide, and the loading rate of single-atom metal is 0.5wt%.

[0118] The difference between Example 24 and Example 19 is that the anti-ultraviolet composition is composed of titanium dioxide doped with surface single-atom metal cerium and titanium dioxide doped with surface single-atom metal zinc in a mass ratio of 1:4.

[0119] The difference between Example 25 and Example 19 is that the anti-ultraviolet composition is titanium dioxide doped with surface single-atom metal cerium + zinc, the carrier is 3000 mesh Anada anatase titanium dioxide, and the loading rate of single-atom metal is 0.5wt%.

[0120] The difference between Example 26 and Example 19 is that the anti-ultraviolet composition is titanium dioxide doped with surface single-atom metal cerium + zinc, the carrier is 3000 mesh Anada anatase titanium dioxide, and the loading rate of single-atom metal is 1wt%.

[0121] The difference between Example 27 and Example 19 is that the anti-ultraviolet composition is titanium dioxide doped with surface single-atom metal cerium + zinc, the carrier is 3000 mesh Anada anatase titanium dioxide, and the loading rate of single-atom metal is 2wt%.

[0122] The difference between Example 28 and Example 19 is that the anti-ultraviolet composition is titanium dioxide doped with surface single-atom metal cerium + zinc, the carrier is 3000 mesh Anada anatase titanium dioxide, and the loading rate of single-atom metal is 3wt%.

[0123] Table 4: Test parameter table of UV-resistant bamboo fiber fabrics in Example 11 and Examples 19-28

[0124]

[0125]

[0126] It can be seen from Example 11 and Examples 19-28 and Table 4 that the surface of anatase titanium dioxide is modified by doping one or more combinations of aluminum, zinc, iron, magnesium, and cerium at the single-atom level, which can improve the prepared bamboo fiber fabric to have excellent anti-ultraviolet effect.

[0127] It can be seen from Example 11 and Examples 19-28 and Table 4 that the loading rate of single-atom-level metal in the surface single-atom metal-doped titanium dioxide is preferably controlled to be 0.5-2wt%.

[0128] Combining Example 11 and Examples 19-28 with Table 4, it can be seen that the surface single-atom metal cerium + zinc doped modified titanium dioxide and the single-atom metal loading rate are 1wt%, which can improve the prepared bamboo fiber fabric and have excellent anti-ultraviolet effect.

[0129] The difference between Example 29 and Example 11 is that the water-based high weather-resistant polyurethane latex includes 2001g of deionized water, 22g of salt-forming agent triethylamine, 300g of acetone, 168.2g of aliphatic diisocyanate HDI, 0.16g of catalyst bismuth isooctanoate, 32.2g of dihydroxymethylpropionic acid, 48.5g of 1,6-hexanediol, 16.2g of tetrafluorobutanediol, 200g of polycarbonate diol CD210 with a molecular weight of 1000, 177.5g of double-end alcohol hydroxyl long-chain alkyl silicone oil IOTA-8865H, 18g of antioxidant BHT, and 20g of leveling agent BYK-S706.

[0130] The difference between Example 30 and Example 11 is that the water-based high weather-resistant polyurethane latex includes 2001g of deionized water, 22g of salt-forming agent triethylamine, 300g of acetone, 168.2g of aliphatic diisocyanate HDI, 0.16g of catalyst bismuth isooctanoate, 26.83g of dihydroxymethylpropionic acid, 37.85g of 1,4-butanediol, 16.2g of tetrafluorobutanediol, 230g of polycarbonate diol CD210 with a molecular weight of 1000, 177.5g of double-end alcohol hydroxyl long-chain alkyl silicone oil IOTA-8865H, 18g of antioxidant BHT, and 20g of leveling agent BYK-S706.

[0131] The difference between Example 31 and Example 11 is that the water-based high weather-resistant polyurethane latex includes 2001g of deionized water, 22g of salt-forming agent triethylamine, 300g of acetone, 168.2g of aliphatic diisocyanate HDI, 0.16g of catalyst bismuth isooctanoate, 32.2g of dihydroxymethylpropionic acid, 60.27g of 1,6-hexanediol, 200g of polycarbonate diol CD210 with a molecular weight of 1000, 190g of hydroxy-terminated methyl vinyl silicone oil IOTA 1203V, 18g of antioxidant BHT, and 20g of leveling agent BYK-S706.

[0132] The difference between Example 32 and Example 11 is that the water-based high weather-resistant polyurethane latex includes 2001g of deionized water, 22g of salt-forming agent triethylamine, 300g of acetone, 168.2g of aliphatic diisocyanate HDI, 0.16g of catalyst bismuth isooctanoate, 26.83g of dihydroxymethylpropionic acid, 37.85g of 1,4-butanediol, 16.2g of tetrafluorobutanediol, 230g of polycarbonate diol CD210 with a molecular weight of 1000, 190g of hydroxy-terminated methyl vinyl silicone oil IOTA 1203V, 18g of antioxidant BHT, and 20g of leveling agent BYK-S706.

[0133] The difference between the control test group and Example 11 is that the water-based high weather-resistant polyurethane latex includes 2001g of deionized water, 22g of salt-forming agent triethylamine, 300g of acetone, 168.2g of aliphatic diisocyanate HD I, 0.16g of catalyst bismuth isooctanoate, 32.2g of dimethylolpropionic acid, 60.27g of 1,6-hexanediol, 250g of polycarbonate diol CD210 with a molecular weight of 1000, 18g of antioxidant BHT, and 20g of leveling agent BYK-S706.

[0134] Table 5: Test parameter table of UV-resistant bamboo fiber fabrics in Example 11 and Examples 29-32

[0135]

[0136] It can be seen from Example 11 and Examples 29-32 and Table 5 that the water-based highly weather-resistant polyurethane latex prepared using the water-based highly weather-resistant polyurethane latex formula provided in the present application and the bamboo fiber fabric prepared using the water-based highly weather-resistant polyurethane latex have excellent anti-ultraviolet effect and relatively long-lasting anti-ultraviolet performance.

[0137] In summary, the present application has excellent anti-ultraviolet effect and relatively long-lasting anti-ultraviolet performance. After 50 washes, it can still maintain ≥90% of the anti-ultraviolet effect. After 2 weeks of simulated aging jungle, the anti-ultraviolet effect retention rate is ≥88%.

[0138] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. An anti-ultraviolet bamboo fiber fabric, characterized by: The surface of the bamboo fiber in the anti-ultraviolet bamboo fiber fabric is attached with an anti-ultraviolet composition via a highly weather-resistant urethane resin; The highly weather-resistant urethane resin is formed by curing water-based highly weather-resistant polyurethane latex; the highly weather-resistant polyurethane latex in the water-based highly weather-resistant polyurethane latex has a particle size of 100-200 nm and a glass transition temperature Tg≤-25°C; The water-based high-weather-resistant polyurethane latex is made of deionized water, a salt-forming agent, acetone, an aliphatic diisocyanate, a catalyst, a chain extender, a polyol composition, an antioxidant, and a leveling agent; the salt-forming agent is ammonia water or triethylamine; the aliphatic diisocyanate is one or more combinations of IPDI, HDI, HMDI, HTDI, and TMDI; the catalyst is organic bismuth or organic tin; the chain extender is dimethylol propionic acid combined with at least one of 1,6-hexanediol, 1,4-butanediol, and tetrafluorobutanediol; the polyol composition includes polycarbonate diol combined with hydroxyl-terminated silicone oil and / or hydroxyl-terminated methyl vinyl silicone oil; The preparation method of the water-based high-weather-resistant polyurethane latex is as follows: at a speed of 100-200 rpm and under nitrogen protection, a polyol composition, an aliphatic diisocyanate, an antioxidant, and a catalyst are sequentially added to a reaction kettle and stirred for 3-5 minutes, the temperature is raised to 92-98° C. for reaction for 3-5 hours, and then a chain extender with accurate measurement is added to continue to react at 92-98° C. for 2-4 hours, and then acetone is added to dilute and the viscosity is adjusted to between 4000-8000 mPa.s, and then a salt-forming agent is added to neutralize after cooling to 40-45° C., and then deionized water and a leveling agent are added to disperse by high-speed shearing, and finally acetone is removed by distillation to obtain a finished product of water-based high-weather-resistant polyurethane latex with a solid content of 25-40%; The anti-ultraviolet composition is composed of surface-doped modified titanium dioxide and titanium dioxide grafted porous silicon nitride in a mass ratio of (3-7):1; The surface-doped modified titanium dioxide comprises titanium dioxide with an average particle size of 0.5-5 μm and modified particles doped on the surface of titanium dioxide with an average particle size of 0.5-5 μm; The modified particles are one or a combination of nano-sized aluminum oxide particles, nano-sized zinc oxide particles, nano-sized iron oxide particles, and nano-sized magnesium oxide particles.

2. The anti-ultraviolet bamboo fiber fabric according to claim 1, characterized in that: The modified particles are nano-sized aluminum oxide particles and / or nano-sized magnesium oxide particles.

3. A process for preparing the UV-proof bamboo fiber fabric according to any one of claims 1 to 2, characterized in that: The following steps are involved: Step 1, preparation of water-based highly weather-resistant polyurethane latex; At the same time, the bamboo fiber fabric is subjected to enzymatic hydrolysis and low-temperature plasma treatment in sequence to obtain a surface-activated modified bamboo fiber fabric, and the surface-activated modified bamboo fiber fabric is immersed in a siloxane aqueous solution for ultrasonic dispersion treatment for 15-30 minutes, wherein the concentration of siloxane in the siloxane aqueous solution is 0.5-2wt%, and the siloxane includes at least one of aminosilane, epoxysilane, methacryloxysilane, and vinylsilane, and the surface-modified bamboo fiber fabric is obtained by drying after ultrasonic dispersion treatment; Step 2, 3-5 parts of water-based high weather-resistant polyurethane latex, 15-20 parts of anti-ultraviolet composition, 0.1-0.2 parts of xanthan gum, and 75-80 parts of deionized water are mixed uniformly to prepare anti-ultraviolet post-solidification solution; Step 3, immersing the surface-modified bamboo fiber fabric in step 1 in the anti-ultraviolet solution, heating to 80-95° C. and immersing for 30-60 minutes, washing and drying to obtain the finished anti-ultraviolet bamboo fiber fabric; Alternatively, in step three, the anti-ultraviolet finishing liquid is applied to the front and back sides of the bamboo fiber fabric respectively, 2-6g of the anti-ultraviolet finishing liquid is applied to each gram of the bamboo fiber fabric, and after the coating is completed, the anti-ultraviolet bamboo fiber fabric is dried at 110-125° C. to obtain the finished product.

Citation Information

Patent Citations

  • Method for preparing finishing agent of modified nano titanium dioxide coating layer of electromagnetic shielding fabric

    CN101768853A

  • Water-based surface polyurethane resin for automobile leather and preparation method of water-based surface polyurethane resin

    CN112341593A

  • Durable antibacterial composite fabric based on graphene and preparation method thereof

    CN113442523A